Social media political usage and political interest of UTAR students - Lee, Rong Wei (2023)
Social media which plays a part in people’s lives can create impact on others by their way of thinking, attitude, and political views to young adults especially University students that are highly relying on it. As the trend of social media and electronic devices has grown rapidly, being able to influence other people’s thoughts and enhance their perspective of political thinking has also increased (Cogburn & Espinoza-Vasquez, 2011). This study focuses on the social media political usage and political interest of UTAR (Universiti Tunku Abdul Rahman) students. More precisely, this study looks into social media components that can increase UTAR students’ general political interest. The data collected was analyzed by descriptive analysis in this study. Considering all the findings, it can be concluded that political issues are not the priority to students when they browse through social media. However, the various elements of social media can spark their political interest. For instance, short videos, social media influencers, podcasts, social blogs, and others. Furthermore, it has been demonstrated that social media influencers have credibility when they publish something related to the politic field and it influences students’ views. It is advised that future study be done with more indepth research.